Why Are They Studying English? Assessing the Goals, Beliefs, Needs, and Attitudes of Adult Immigrants in ESL Programs - Olga D. Lambert (Adult Education Research Conference, 2008)
The purpose of this study was to develop and pilot a questionnaire for limited English proficient adults that would 1) provide adult ESL programs with information about their students' goals, needs, and attitudes and 2) enable large-scale data collection among these students for both program planning and research purposes.
Keywords: ESL; immigrants; goals; beliefs; needs; attitudes